Media Sosial bagi Desa Wisata: Sebuah Kajian Konseptual - Wijaya, Stefanus Wisnu (Sanata Dharma University, 2016)
Social media is the application of information technology that has revolutionized the tourism business. The role of social media in the tourism business has been able to change the pattern of tourism businesses, even small to facilitate tourism industry to compete. However, this situation has not received an adequate response from the Indonesian tourism industry represented by the ICT readiness index is still low. This shows that the capability of human resources in the use of ICT including social media applications are still low. For that we need an approach that is able to increase literacy social media for the tourism industry, particularly small scale industries such as tourism village. Tourism Village has a unique characteristic among the tourism industry. Village tourism industry based on strong social capital among industry players tourist village. So that the process of improving the management capacity of rural tourism situation should be able to tune the social environment of rural tourism for the purpose of social media literacy peningkatana capacity can be achieved. The approach of participatory action research is considered in accordance with the characteristics of a tourist village. Involvement of researchers and research subjects in the process of improving literacy social media, especially during the process of mentoring and reflection are considered to help achieve the objectives of the study.